2006
DOI: 10.1097/01.opx.0000237546.88464.6d
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Progression and Spatial Repeatability of Tear Breakup

Abstract: Structural influences such as the "black line" or corneal lid defects appeared to influence the recurrence of breakup in the same region. The S-TBUD quantitative image analysis technique demonstrates that the tear film of subjects with dry eye continues to rapidly destabilize after an initial first break; thus, a low TBUT was combined with a high DAGR. The central corneal region of subjects with dry eye appeared especially susceptible to increased tear breakup when compared with controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 38 publications
3
54
2
Order By: Relevance
“…23 Subjects were then seated behind a slit lamp biomicroscope fitted with a digital video camera, and 2 lL of sodium fluorescein (2%) was pipetted into the tested eye while the other eye was patched shut. As in previous studies, subjects were asked to keep the tested eye open as long as possible 20,21 while they turned a knob (potentiometer) to indicate the level of discomfort in the tested eye on a 0 to 10 scale (0 ¼ no discomfort and 10 ¼ very uncomfortable). 22 Following each trial, subjects rated their overall discomfort on separate integer scale of 1 (no discomfort) to 10 (very uncomfortable) and then indicated the level of irritation, stinging, burning, pricking, and cooling on visual analogue scales (VAS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Subjects were then seated behind a slit lamp biomicroscope fitted with a digital video camera, and 2 lL of sodium fluorescein (2%) was pipetted into the tested eye while the other eye was patched shut. As in previous studies, subjects were asked to keep the tested eye open as long as possible 20,21 while they turned a knob (potentiometer) to indicate the level of discomfort in the tested eye on a 0 to 10 scale (0 ¼ no discomfort and 10 ¼ very uncomfortable). 22 Following each trial, subjects rated their overall discomfort on separate integer scale of 1 (no discomfort) to 10 (very uncomfortable) and then indicated the level of irritation, stinging, burning, pricking, and cooling on visual analogue scales (VAS).…”
Section: Methodsmentioning
confidence: 99%
“…20,21 For this analysis, TBU was defined in the traditional clinical sense, as areas of dark spots, streaks, or amorphous areas in the fluorescent corneal tear film. 29,30 A clinically trained observer masked to subject and trial information identified the threshold PI that included all areas of TBU in the final image of each trial.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The tear film is usually studied in the inter-blink period, where an unstable tear film quickly becomes evident as TBU progresses rapidly (Liu et al, 2006). This is measured clinically by fluorescein tear break-up time (TBUT), or the first appearance of a dark or “dry spot” after a blink (Norn, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…(6, 40, 41) Briefly, color fluorescent images were converted to grayscale, and the region of total exposed cornea (region of interest) outlined. A custom MATLAB® program was used to calculate the percentage of TBU using a threshold pixel intensity set by the investigator for each trial.…”
Section: Methodsmentioning
confidence: 99%